1975
DOI: 10.1038/bjc.1975.23
|View full text |Cite
|
Sign up to set email alerts
|

Methanol extraction residue of BCG in the treatment of transplanted rat tumours

Abstract: Summary.-Subcutaneous growth of immunogenic chemically induced rat sarcomata and a hepatoma was restricted when cells were injected into syngeneic animals in admixture with MER. Rats rejecting mixed inocula were immune to further challenge with the same tumour. Growth of a chemically induced mammary carcinoma which lacks detectable immunogenicity was suppressed when low cell inocula were injected in admixture with MER or intact BCG organisms, although animals were not immdne to re-challenge. These studies indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 14 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Most importantly, intrapleurally injected BCG markedly prolongs survival of rats receiving intrapleural tumour cell injections, but repeated treatment by active immunotherapy using viable or radiation-killed tumour cells mixed with BCG was relatively ineffective and, moreover, did not augment the effect of intrapleurally injected organisms. The MER of Weiss and Wells (1960) was also effective in the pleural cavity, extending the previous report on its tumoursuppressive action when injected s.c. mixed with tumour cells (Hopper, Pimm and Baldwin, 1975).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, intrapleurally injected BCG markedly prolongs survival of rats receiving intrapleural tumour cell injections, but repeated treatment by active immunotherapy using viable or radiation-killed tumour cells mixed with BCG was relatively ineffective and, moreover, did not augment the effect of intrapleurally injected organisms. The MER of Weiss and Wells (1960) was also effective in the pleural cavity, extending the previous report on its tumoursuppressive action when injected s.c. mixed with tumour cells (Hopper, Pimm and Baldwin, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatoma D23, originally induced by 4-dimethylaminoazobenzene in an adult male rat of the Department's inbred Wistar strain, was used in the present studies, in its ascitic form, maintained by weekly i.p. passage of 107 tumour cells (Robins, 1975 (Hopper, Pimm and Baldwin, 1975 (Baldwin and Pimm, 1973a (Fig. 3).…”
Section: Methodsmentioning
confidence: 99%
“…The MER fraction of phenol-killed BCG (Phipps strain) w%as used in these experiments. MER has been previously show,n to possess nonspecific humoral and cellular immunological adjuvant properties in a variety of animals (Ben-Efraiin et al, 1973;Kuperman et al, 1972), and has recently been used successfully in tumour immunotherapy in both animals and man (Hopper et al, 1975;Cohen et al, 1975;Weiss et al, 1975). MER was a gift from the division of Cancer Treatment, National Cancer Institute, Bethesda, Md.…”
Section: Methodsmentioning
confidence: 99%
“…Both intact Bacillus Calmette-Guerin (BCG) and the methanol extraction residue (MER) (Weiss and Wells, 1960) of BCG have had extensive application in recent years in tumour immunoprophylaxis and immunotherapy (Mathe, Pouillart and Lapeyraque, 1969;Bast et al, 1974;Haran-Ghera and Weiss, 1973;Hopper, Pimm and Baldwin, 1975). Treatment with MER non-specifically stimulates both the humoral and cellular immune systems (Ben-Efraim, Constantini-Sourojon and Kuperman et al, 1972), and has been shown to be successful in tumour immunotherapy in a number of animal models.…”
mentioning
confidence: 99%
“…MER has been previously shown to possess non-specific immunological adjuvant properties in a variety of animals (Weiss, 1972;Ben-Efraim et al, 1973), and has been successfully used in tumor immunotherapy in both animals and man (Weiss, 1972; Haran-Ghera and Hopper et al, 1975;Weiss et al, 1975). MER was provided as a gift by the Division of Cancer Treatment, National Cancer Institute, Bethesda, Maryland.…”
Section: Methanol Extraction Residue (Mer)mentioning
confidence: 99%